Statistics of Poland – the First Yearbook of Polish Lands: Authors and Content - Pociecha, Józef (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The beginning of the twentieth century is a time of the development of official statistics in European countries. Due to the lack of its own independent state, it was not possible to publish a Yearbook of Poland at the time. In this context, the Polish Statistical Association (PSA) was founded in Cracow in 1912. One of its main tasks was to merge statistical information on Polish lands dispersed among statistical offices of Russia, Germany and Austria and to issue its own statistical yearbooks for Polish lands and their population. Before the beginning of World War I, the PSA was able to prepare the publication Statistics of Poland, printed in 1915, whose main authors were: A. Krzyżanowski and K. W. Kumaniecki. Many people from the intellectual elite of the country were involved in the project. The territorial scope of Statistics of Poland is interesting. It covers the territory of the first Polish Republic and the area of Upper Silesia and the southern Masuria, where Poles were the majority. Statistical data contained in Statistics of Poland amaze by their abundance even today. The importance of Statistics of Poland is that it gave arguments for the Polish delegation in the conduct of the discussions on the shape of the territory of reborn Poland in 1918 carried out at the peace conference in Versailles.